A DOFS-Based Approach to Calculate the Height of Water-Flowing Fractured Zone in Overlying Strata under Mining. (17th March 2021) - Piao, Chunde; Li, Jinjun; Wang, Dangliang; Qiao, Wei
Abstract : The distributed optical fiber sensing (DOFS) is a technique that can obtain full spatial and temporal information concerning the behavior of a large range of measurand fields along a fiber path and realize the distributed monitoring of the overburden section under mining. To calculate the height of water-flowing fractured zone caused by the exploitation of coal, this study employed distributed optical fiber sensors with OSI-C-S optical frequency domain reflectometry (OFDR) technology and designed a similar-material model test based on the engineering geological conditions of Daliuta Coal Mine. Through the test, deformation characteristics of overlying strata were studied, the linear relationship was summarized between the strain gradient and the shear stress measured by fiber sensors when the rock layer cracks, and a method was proposed of using the measured strain to measure the height of the water-flowing fractured zone in overlying strata. The test results show that there are several locations where the sign of the shear stress changes (positive to negative or vice versa) in the overlying strata during the initial stage of coal seam mining. As the working face advanced, the change locations gradually concentrated at the place where the rock cracks. By identifying the breakpoints of the rock and the locations where the sign of the shear stress measured by fiber sensors changes, this paper calculated the height of the water-flowing fractured zone in Daliuta Coal Mine. After comparing the height with the abscission layer position in the model test and the predicted height by the empirical formulas in the specification, it has been found that the three results are basically consistent, which in turn verifies the accuracy of this method.